Specific executive control impairments in Tourette syndrome: The role of response inhibition. (February 2017) - Yaniv, Asaf; Benaroya-Milshtein, Noa; Steinberg, Tamar; Ruhrrman, Dafna; Apter, Alan; Lavidor, Michal
Highlights: Response inhibition in TS patients was impaired, beyond comorbid conditions effect, and predicted symptoms severity. Other executive impairments attributed to TS can be explained as a deficit in the response inhibition component. Response inhibition might play a crucial role in tics reduction. Abstract: Background: Tourette syndrome (TS) is a childhood-onset disorder characterized by motor and vocal tics. While cognitive features of common comorbid conditions such as attention deficit hyperactive disorder and obsessive compulsive disorder have been widely investigated, the cognitive profile of TS patients remains to be precisely defined. In this regard, the executive functions system (EF) is of especial interest. Aims: The aim of the study was to delineate the various components of executive processes in adult TS patients. Methods: A sample of 19 adults diagnosed with TS and 19 age-matched control subjects underwent computerized battery of executive tasks, as well as block design and memory tests. All patients received a thorough clinical assessment with an emphasis on illness severity. Results: There was a marked impairment in response inhibition ability regardless of comorbid conditions, In addition, there was decreased accuracy in set shifting, but not in response time. These results imply that impaired response inhibition in the EF system is the primary cognitive impairment in TS and that many of the previously reported impaired executive functions in TS are secondary to this impairment. Conclusions: This finding of impaired response inhibition in TS may imply that rehabilitation of this inhibition component could prove to be an important therapeutic strategy in adults with TS.